Diagnostic Accuracy of Clinical Pallor to Detect Anemia among Pregnant Females Seeking Antenatal Care in a Tertiary Care Hospital - Hira Bashir, Hira Afreen, Tanzila Fahim, Shazia Shams, Shireen Butta, Haleema Yasmin (Pakistan Journal of Medical & Health Sciences, 2022)
Background: One-third of the world’s population is affected by anemia, and the vast majority of those who suffer from it live in developing countries. Eye, nail bed, facial, and palmer wrinkle coloration are some of the most classic indicators used to diagnose anemia in patients. This study is design to determine diagnostic accuracy of clinical pallor to detect anemia among female. If results of this study show high accuracy for clinical pallor to detect anemia, with different ethnic background and color complexion, testing for pallor can be used as an effective alternative method. Objective: The goal of this study is to investigate the usefulness of clinical pallor in identifying anemia in pregnant women who attend the outpatient department of a tertiary care hospital, with the level of blood hemoglobin serving as the gold standard. Methodology: Settings: Department of Gynecology and Obstetrics Ward 8, Jinnah Postgraduate and Medical Centre, Karachi. Duration: 06 Months from 29-03-2017 to 29-09-2017 Design: Cross sectional Validation Study Subject and Methods: There were 393 pregnant women that participated in this study. They all sought prenatal care at the Emergency Clinic or the Outpatient Department. Hemoglobin concentrations in the patient’s blood were recorded in the investigation’s chart as the reference variable. On the same day five milliliters of blood was drawn for assessment of iron deficiency anemia. Tubes were transported to the laboratory of the hospital. Results of the laboratory tests were evaluated when available. Results: The average age of the patients was 28.17±5.07 years. Sensitivity, specificity, PPV, NPV and accuracy of clinical pallor was 94.1%, 51.9%, 40.7%, 96.2% and 62.8% respectively. Conclusion: Finally, even if hemoglobin or hematocrit levels cannot be measured directly, clinical pallor examination can still be performed. This is a good way to tell if a person is suffering from severe anemia. Clinical pallor of the palms is superior than clinical pallor of the buccal mucosa, nail bed, or conjunctiva in the diagnosis of mild and severe anemia in children. Nail bed and conjunctival clinical pallor is less common. Medical professionals who are new to clinical pallor might learn about its diagnosis and management by observing it from multiple angles.